Study guides

☆☆

Q: What is the foil method of (x plus 3)(x minus 3)?

Write your answer...

Submit

Still have questions?

Related questions

Assuming there should have been a plus or minus sign between 4x2and 3x, the answer is: a binomial.Assuming there should have been a plus or minus sign between 4x2and 3x, the answer is: a binomial.Assuming there should have been a plus or minus sign between 4x2and 3x, the answer is: a binomial.Assuming there should have been a plus or minus sign between 4x2and 3x, the answer is: a binomial.

x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)

(x + 3)(3x - 2)

3x - 5x + x = -x

the answer is -174

I think you mean (3x ± 1)^2 = (3x+1)(3x-1)?

15x minus 8=minus 180 3x+8=24

This simplifies to 3x-6+4y.

(3x - 1)(x + 2)

(3x-2)(x-2)

(x + 2)(3x - 1)(3x + 1)

Because (x plus 3x) is 4x, and (-5 + 11) is 6.

3x - 12 = 10x - 15 - 6x -10 3x - 12 = 4x -25 3x + 13 = 4x 13 = 4x - 3x 13 = x None?

4x + 10 + 3x = 40 - 3x 4x + 10 + 3x + 3x = 40 20x = 40 x = 2

It can be simplified to: 2x+2

(x2 + 3x + 5)(x2 - 3x + 4)

3x^2 -14x +15 = (3x-5)(x-3)

Collect like terms: 3x - x + 4x - 4y + 6y + 2 = 6x + 2y + 2

5x + 4

eq: 3x+5=7 =3x=7-5 =3x=2 =x=2/3

20x2 - 3x + 10 does not have any real factors.

3x+7=2x-5 x=-12

That can be factored to (3x - 5)(3x - 5) or (3x - 5)2

Factorise it: (x + 5)(3x - 8)

-6 + 3x - y - 4x + 4y + 5 (combine like terms) = (-6 + 5) + (3x - 4x) + (-y + 4y) = -1 - x + 3yHope this helps :)